ANALISIS KINERJA SURAT BERHARGA SETELAH PENAWARAN PERDANA (IPO) DI INDONESIA - Arum Prastiwi; Indra Wijaya Kusuma (Journal of Indonesian Economy and Business (JIEB), 2001)
Numerous studies examined the performance of initial public offerings in some countries. The studies documented two phenomenon: short-run underpricing and long-run underperformance. The purpose of this study is to investigate stocks performance after Initial Public Offerings (IPO) in Indonesia. Monthly abnormal return was used as a proxy for performance using Market-Adjusted Model. The short term performance is based on the 3 months performance and the long-term performance is based on 24 months. The number of the sample is 78 company that issued IPO in 1994 – 1997. Results from one sample t-test show that in the short run there are large positive mean and median excess returns of 39.07 percent and 21.04 percent respectively. The long run mean abnormal return was dropped until –238.83 percent and –243.22 percent respectively for stocks that were bought in the initial market and in the aftermarket. This result is consistent with studies in numerous countries. In the long run, the performance was underperformed. Result from paired comparison t-test confirms that in the long run the performance was worse (underperformed) than in the short run.